Older Adults in the Cardiac Intensive Care Unit: Factoring Geriatric Syndromes in the Management, Prognosis, and Process of Care: A Scientific Statement From the American Heart Association - Damluji, Abdulla A; Forman, Daniel E; van Diepen, Sean; Alexander, Karen P; Page, 2nd, Robert L; Hummel, Scott L; Menon, Venu; Katz, Jason N; Albert, Nancy M; Afilalo, Jonathan; Cohen, Mauricio G (Circulation (New York, N.Y.), 2020)
Longevity is increasing, and more adults are living to the stage of life when age-related biological factors determine a higher likelihood of cardiovascular disease in a distinctive context of concurrent geriatric conditions. Older adults with cardiovascular disease are frequently admitted to cardiac intensive care units (CICUs), where care is commensurate with high age-related cardiovascular disease risks but where the associated geriatric conditions (including multimorbidity, polypharmacy, cognitive decline and delirium, and frailty) may be inadvertently exacerbated and destabilized. The CICU environment of procedures, new medications, sensory overload, sleep deprivation, prolonged bed rest, malnourishment, and sleep is usually inherently disruptive to older patients regardless of the excellence of cardiovascular disease care. Given these fundamental and broad challenges of patient aging, CICU management priorities and associated decision-making are particularly complex and in need of enhancements. In this American Heart Association statement, we examine age-related risks and describe some of the distinctive dynamics pertinent to older adults and emerging opportunities to enhance CICU care. Relevant assessment tools are discussed, as well as the need for additional clinical research to best advance CICU care for the already dominating and still expanding population of older adults.